Negative Politeness Strategy on Expressive Act of Rosiana Silalahi Talk Show - Nurul Aini nurul; Djatmika; Sumarlam; Diah Kristina (Faculty of Language and Literature, University of Surakarta, 2022)
Rosi talk show was a conversation program that presented Indonesian politics with supporting and opposing government arguments. The objectives were to find expressive acts and to explain how expressive acts performed negative politeness in the Rosi talk show. The theories used politeness strategy by Brown and Levinson (1987) on negative politeness in expressive act by Searle (1975) by the moderator. This study used qualitative content analysis, and the location was YouTube Channel KompasTV. The data were the moderator utterances involving expressive acts representing negative politeness. This research was a purposive sampling technique focussing on three segments in ‘student’s demonstration and Ade Armando percussion’. The data collection technique was free to engage in conversation to transcribe data audio into written, and Focus Group Discussion (FGD) was used to know the moderator's politeness tendencies. This study used an interactive method by Miles&Huberman (1992) to conclude. The result showed 18 expressive acts with six sub-strategy of negative politeness. Then, seven expressive speech acts: thanking, apologising, blaming, praising, showing sympathy, and accusing. Next, the dominant moderators’ expressive act was blaming. While there are four sub-negative politeness strategies: indirect, making pessimism, minimising impositions, and apologising. The researcher found that negative politeness strategies were realised with expressive acts using suspecting to interact with pros participants.